Strategi Desa Dalam Pengembangan Sektor Usaha Kecil Menengah (UKM) Di Desa Puain Kanan Kecamatan Tanta Kabupaten Tabalong - Mirnayanti, Saumira (stiatabalong.ac.id, 2026)
The program implemented by the Small and Medium Enterprises Cooperative Agency since 2012 has carried out various efforts to improve the quality of SMEs, namely through entrepreneurship training programs. This research was conducted based on the enormous potential of small and medium enterprises (SMEs), which play a strategic role in national economic development. In addition to contributing to economic growth and employment, they also play a role in the distribution of development outcomes. The purpose of this study is to identify and describe the strategies implemented by Puain Kanan Village, Tanta Subdistrict, Tabalong Regency in developing the Small and Medium Enterprises (SME) sector. The research method used was descriptive, employing a qualitative approach. The analysis used in this study was SWOT analysis. Success in obtaining data or information from the research subjects was highly dependent on the researchers' ability to conduct interviews. In this study, the researchers conducted interviews with the Head of Puain Kanan Village, the Head of the Small and Medium Enterprise Development Division, and small and medium enterprise owners. The results of research on Village Strategies in Small and Medium Enterprise Development in the Puain Kanan Village Industrial Center, Tanta District, Tabalong Regency, show that industries that absorb a lot of labor, such as small and medium enterprises, can be used as a source of livelihood in villages, Therefore, the role of the village government is needed in the development of small and medium enterprises. Based on the results of this analysis, it is hoped that the village government of Puain Kanan, Tanta District, Tabalong Regency, can provide assistance to industry players in the village in obtaining capital loans. To overcome problems in development, it is hoped that the village government will conduct regular training